Bebidas açucaradas, alimentos processados e/ou ultraprocessados e sua relação com o perfil lipídico - Cardoso, Isadora Bianco (2018)
The diet has influence like a risk factor for cardiometabolic health, which cause damage to the health and economy in several countries. Atherosclerotic cardiovascular disease (CAD) are the principal cause of death and disability in Brazil and worldwide according to the World Health Organization (WHO). Environmental factors such as lifestyle, including inadequate diet and decreased physical activity, influences traditional risk factors for CAD. Inadequate dietary patterns, that predominate processed and ultraprocessed foods, rich in saturated fat, trans, simple carbohydrates (especially added sugars) whose consumption has received attention as contributors to the development of cardiovascular risk factors. Therefore, seeing the increase consumption of ready-to-eat foods in the diet of individuals, this study aimed to evaluate the interaction of these foods with cardiovascular health, especially in the alteration of serum lipids. This dissertation presents two parts: a review chapter of the literature that deals with food processing and its impact on cardiovascular health; and a result article refers to a systematic review with cohort studies to verify the association of changes in lipid profile with consumption of sugar sweetened beverage, processed and/or ultraprocessed foods which revealed that majority of studies (69 %) showed a negative impact of the consumption of these foods and drinks on the serum lipid levels of adult from different countries. A reduction consumption is relevant to public health, especially in the context of modifying risk factors that have synergistic effects in terms of cardiovascular risk. This study complete an important gap, about the effect of consumption of processed and/or ultraprocessed foods and sugary drinks on the serum lipid profile, whose condition, like dyslipidemia, has repercussions on a wide spectrum of cardiometabolic disorders promoters of CAD.